2021
DOI: 10.3389/ffunb.2021.671796
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Fusapyrone Depends on the H3K9 Methyltransferase, FmKmt1, in Fusarium mangiferae

Abstract: The phytopathogenic fungus Fusarium mangiferae belongs to the Fusarium fujikuroi species complex (FFSC). Members of this group cause a wide spectrum of devastating diseases on diverse agricultural crops. F. mangiferae is the causal agent of the mango malformation disease (MMD) and as such detrimental for agriculture in the southern hemisphere. During plant infection, the fungus produces a plethora of bioactive secondary metabolites (SMs), which most often lead to severe adverse defects on plants health. Change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 115 publications
0
21
0
Order By: Relevance
“…In F. fujikuroi the ortholog of KMT6 appears to be essential (Studt et al 2016a , b ), but similarly to F. graminearum , down-regulation of KMT6 by RNA interference resulted in up-regulation of several otherwise silent secondary metabolite genes, a phenotype that was accompanied by reduced H3K27me3 levels at the respective gene loci and the production of novel compounds (Studt et al 2016a , b ). Notably, H3K9me3 established by Kmt1 appears to be essential for biosynthesis of fusapyrone in Fusarium mangiferae associated with mango malformation (Atanasoff-Kardjalieff et al 2021 ). Another histone mark that has received little attention in filamentous fungi is H4K20me3 associated with gene silencing in higher eukaryotes (Kourmouli et al 2004 ; Schotta et al 2004 ).…”
Section: Advances In the Molecular Regulation Of The Biosynthesis Of ...mentioning
confidence: 99%
“…In F. fujikuroi the ortholog of KMT6 appears to be essential (Studt et al 2016a , b ), but similarly to F. graminearum , down-regulation of KMT6 by RNA interference resulted in up-regulation of several otherwise silent secondary metabolite genes, a phenotype that was accompanied by reduced H3K27me3 levels at the respective gene loci and the production of novel compounds (Studt et al 2016a , b ). Notably, H3K9me3 established by Kmt1 appears to be essential for biosynthesis of fusapyrone in Fusarium mangiferae associated with mango malformation (Atanasoff-Kardjalieff et al 2021 ). Another histone mark that has received little attention in filamentous fungi is H4K20me3 associated with gene silencing in higher eukaryotes (Kourmouli et al 2004 ; Schotta et al 2004 ).…”
Section: Advances In the Molecular Regulation Of The Biosynthesis Of ...mentioning
confidence: 99%
“…We have previously shown that the cryptic FmPKS8 is expressed in low nitrogen conditions, and that its expression depends on a functional ortholog of FmKmt1 [17] . To identify possible FmPKS8‐derived products, an untargeted metabolomics approach was used.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that FmPKS8 expression greatly depends on the nitrogen source and concentration i. e., FmPKS8 expression is specifically induced in liquid ICI medium with 6 mM NaNO 3 as sole nitrogen source ( FmPKS8 ‐inducing conditions). While only low or no transcripts are detectable when either 6 or 60 mM glutamine or 120 mM NaNO 3 is used [17] . To further validate the FmPKS8 origin of compound 1 – 9 , FmWT was grown for seven days under these different nitrogen supply conditions, and culture filtrates were subsequently analyzed by targeted chemical analysis via HPLC‐HRMS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations